Effect of QR Code Scan-Based 3D Puzzle Media on Learning Outcomes in Class V Science Learning in Elementary Schools: Media Puzzle 3D Berbasis Scan QR Code Terhadap Hasil Belajar Pada Pembelajaran IPA Kelas 5 di Sekolah Dasar - Sholicahah, Maratus; Setiyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine whether there is an effect of scan barcode based 3D Puzzle Media on Learning Outcomes in 5th Grade Students of SDN Krembung 1 Science Learning. This type of research is a quantitative experiment with the type of pre-experimental designs in the form of one-group pretest-posttest design. The instrument in this study uses pretest and posttest test instruments. The samples in this study were grade 5 students at SDN Krembung 1. The results showed that there was an effect of audio-visual-based 3D puzzle media on learning outcomes in science learning which was obtained t count = 2.052, then obtained t table 1729. Because 2,052 > 1,729 Ho is rejected and Ha is accepted, it means that there is a significant difference. From the calculation results of the normlized g > 0.70 test which interprets the high (high) effect of using audio-visual-based 3D puzzle media on learning outcomes in science learning. To find out how much influence scan barcode 3D puzzle media has on learning outcomes in science learning, 5th grade students of SDN Krembung 1 can see in the table n gain score % which interprets the use of puzzle media on learning outcomes in science learning as much as 70.71%.